Research on the Dilemma and Optimization Path of Traffic Safety Management on College Campus - Luo, Qing (Journal of Social Science and Humanities, 2024)
With the rapid economic and social development and the enrollment expansion of colleges and universities year after year, the campus traffic safety problems are increasing, and the contradiction between people, cars and roads on campus is becoming more and more prominent. Campus traffic safety problems need to be solved urgently, and it is very important to optimize the campus traffic management in colleges and universities. On the basis of summarizing the characteristics and significance of campus traffic management, this paper further explores the practical predicament of campus traffic safety management, and puts forward a systematic optimization path of campus traffic management.